Differential effects of anthropogenic noise and vegetation cover on the breeding phenology and success of two urban passerines - Monniez, Emmanuelle; Jiguet, Frédéric; Vignal, Clémentine; Biard, Clotilde (Frontiers in Ecology and Evolution, 2022)
The urban environment is associated with a multitude of challenges and stressors for populations of wild species from the surrounding natural environment. Among those, habitat fragmentation and noise pollution are suspected to have negative effects on the behavior and physiology of free-living birds in urban areas. Chronic exposure and exposure early in life to anthropogenic noise could be particularly deleterious, with short- and long-term consequences. In this study, we investigated if noise levels in city parks affect the distribution and reproductive success of two common bird species in the urban environment, the great tit (Parus major) and the blue tit (Cyanistes caeruleus) and if vegetation cover could mitigate those effects. We predicted that high noise levels might correlate with a decreased nest-box occupancy rate, a delayed laying date or a decreased clutch size, hatching and fledging success. On the contrary, vegetation cover was expected to correlate positively with nest occupancy rate, advanced laying date, increased clutch size, hatching, and fledging success. We used data from population monitoring collected between 2012 and 2019 in parks and green public spaces in the city center and suburbs of Paris, France, and did not find any correlation between nest occupancy rates and noise levels or vegetation cover for both species. Laying date was not significantly related to anthropogenic noise in any species but increased with vegetation cover in the great tit, while we did not find any association with clutch size. Hatching success in blue tits negatively correlated with increasing noise levels, and positively with increasing vegetation coverage. Finally, we did not find any correlation between anthropogenic noise or vegetation cover and the clutch size or fledging success in both species. In this study, two closely related species that share a common environment show a different sensibility to environmental parameters during reproduction, a key period for population maintenance. It also highlights the importance of considering multiple parameters when studying wild populations living in the urban environment.